2021
DOI: 10.1177/20503121211036132
|View full text |Cite
|
Sign up to set email alerts
|

Community risk perception and health-seeking behavior in the era of COVID-19 among adult residents of Harari regional state, eastern Ethiopia

Abstract: Background: COVID-19 brought significant challenges to public health. It changed the view of global health and safety, trust in the healthcare system, and clients’ willingness to seek healthcare. To contain the course of the COVID-19 pandemic and its detrimental effects, understanding peoples’ health behavior, especially healthcare-seeking, and determining the community risk perception is very important. Thus, this study aimed to determine the health-seeking behavior, community’s risk perception to COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
10
2
Order By: Relevance
“…This perspective is supported by a recent study in Ethiopia that found a significant association between education level and COVID‐19 risk perception 23 …”
Section: Resultssupporting
confidence: 57%
“…This perspective is supported by a recent study in Ethiopia that found a significant association between education level and COVID‐19 risk perception 23 …”
Section: Resultssupporting
confidence: 57%
“…This is because waiters are more vulnerable due to contact with almost all individuals, especially foreigners who enter hotels and restaurants (Asefa et al 2020 ). This result is also lower than from another local study (Eyeberu et al 2021 ). The difference in the study setting and data collection questionnaire accounted for this discrepancy.…”
Section: Discussioncontrasting
confidence: 67%
“…Many previous studies investigated sociodemographic determinants of COVID-19 risk perception. Women, the elderly, wealthy people, and those with underlying diseases were more likely to have a higher risk perception of COVID-19 ( Eyeberu et al, 2021 ; He et al, 2021 , Monge-Rodríguez et al, 2021 ; Zeballos Rivas, Lopez Jaldin, Nina Canaviri, Portugal Escalante, Alanes Fernandez, et al, 2021 ). Second, risk perception is associated with psychological factors.…”
Section: Introductionmentioning
confidence: 99%